Using the unbiased perspectives of people living with a spinal cord injury in assessments of mobility - Booth, H.; Harvey, L.; Denis, S.; Barratt, D.; Allison, Garry; Adams, R. (2013)
Study design:Clinometrics study.Objective:To devise a way of capturing the unbiased perspectives of people living with a spinal cord injury (SCI) in assessments of mobility.Setting:SCI unit and community.Methods:Three groups of raters used the Global Impression of Change Scale (GICS) to rate change in mobility of a cohort of patients with a recent SCI. The three groups of raters were as follows: 10 people with a recent SCI, 10 people with an established SCI and 10 physiotherapists. The ratings were done after viewing 51 pairs of videos depicting one of three motor tasks: sitting unsupported, transferring and walking. Each pair of videos showed the same person performing the same motor task on two occasions. The videos were taken between 1 h and 5 months apart and presented side by side, randomly left or right, on the screen. Raters were asked to score the amount of change in performance between the two videos on a 7-point Global Impression of Change Scale (GICS). Intra-rater reliability for the three motor tasks and three groups of raters was determined using intra-class correlation coefficients.Results:People with an SCI were reliable at rating change in patients' abilities to transfer and walk with ICC's ranging from 0.66 to 0.81 (95% Confidence interval bounds ranging from 0.51 to 0.94). Physiotherapists were consistently but only marginally more reliable at rating than people with an SCI.Conclusions:Videos and the GICS may provide a way of using the unbiased perspectives of people living with spinal cord injury in assessments of mobility. © 2013 International Spinal Cord Society All rights reserved.